2021
DOI: 10.1177/2325967121999464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decreasing the Anterior Pelvic Tilt on Range of Motion in Femoroacetabular Impingement: A Computer-Simulation Study

Abstract: Background: The influence of pelvic tilt mobility, which can be reproduced in computer-simulation models, is an important subject to be addressed in the understanding of femoroacetabular impingement (FAI) pathophysiology. Purpose: To use computer-simulation models of FAI cases to evaluate the optimum improvement in hip range of motion (ROM) achieved by decreasing the anterior pelvic tilt and compare the results with the improvement in ROM achieved after cam resection surgery. Study Design: Controlled laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…Computer simulation for kinematics is a powerful tool that has been applied to virtual osteochondroplasty in femoroacetabular impingement (FAI), 9 identification of the impingement point, 10 and assessments of the effect of pelvic mobility in FAI. 11,12 While there are several limitations, as listed below, computer simulation is effective, particularly when used to quantify ROM and bony impingement. To the best of our knowledge, no previous study has applied computer simulation analysis for evaluation after shelf acetabuloplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Computer simulation for kinematics is a powerful tool that has been applied to virtual osteochondroplasty in femoroacetabular impingement (FAI), 9 identification of the impingement point, 10 and assessments of the effect of pelvic mobility in FAI. 11,12 While there are several limitations, as listed below, computer simulation is effective, particularly when used to quantify ROM and bony impingement. To the best of our knowledge, no previous study has applied computer simulation analysis for evaluation after shelf acetabuloplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Given these results, we examined the effects of a 10° change in pelvic tilt. In a previous study, we conducted a dynamic simulation analysis to compare improvements in ROM (ie, MIR) between cam resection models and models of a 10° change in St. 16 Cam resection models were based on postoperative CT scans (cam resection surgery). We showed that a change in posterior St of 10° was as effective as cam resection at reducing impingement; however, a change of only 5° was not as effective as cam resection.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical question arising here was “Should physical therapy that considers 3-dimensional (3D) complex mobility rather than just sagittal mobility be performed in patients with FAI?” The purpose of this study was to use simulation analysis to examine and compare the effect of 3D changes versus a single-plane change (ie, sagittal tilt [St]) in pelvic movement on hip ROM in patients with FAI. Because the effect of sagittal posterior tilt on improving hip ROM has been well demonstrated, 16,33,37 we focused on the comparison between complex 3D change and sagittal posterior tilt change. We hypothesized that the combination of 3D planar mobility (ie, St, axial rotation [Ar], and coronal tilt [Ct]) would lead to more effective resolution of biomechanical impingement, with small changes (5°) in 3D motion rather than a large change (10°) in a single direction (ie, sagittal).…”
mentioning
confidence: 99%
See 2 more Smart Citations